1590 Inguinal Hernia in "Girls" Rarely Reveals Complete Androgen Insensitivity Syndrome. (October 2012) - Kalfa, N; Paris, F; Andreica, A; Audran, F; Maillet, O; Philibert, P; Galifer, RB; Sultan, C
Abstract : Background Aim: According to literature, the incidence of complete androgen insensitivity syndrome (CAIS) revealed by inguinal hernia in "girls" is variable due to the clinical heterogeneity of the series. The aim of this study is to estimate the percentage of CAIS in children with female phenotype who presented with various forms of hernias. Material and Methods: This is a retrospective study based on a population of 129 "girls" treated for bilateral hernia repair. The gonads were assessed either by preoperative US or by intra operative direct examination. In case of CAIS suspicion, gonadic tissue was sampled, karyotyping and hormonal analysis were performed. Diagnosis of CAIS was confirmed by direct AR gene sequencing (exons 1–8). Results: We identified 2 cases of CAIS (mutations pS204N+delR615 and del F584). The percentage of CAIS depends on the population involved. On the entire series (including simple permeability of the peritoneo-vaginal channel, n=129), the rate of CAIS is low, 1.6%. In case of clinical bilateral hernia whatever the content, digestive or gonadal, the rate of CAIS climbs at 6.9%. For the bilateral gonadic hernias (n=7), the rate of CAIS is 28.6%. Conclusions: The incidence of CAIS among "girls" undergoing bilateral hernia repair is low and varies according to the involved population. The simple permeability of the contralateral channel is not a significant risk factor for CAIS. Systematic research of CAIS may be justified in a small number of patients, especially those with bilateral gonadal content. Visualization of the gonads remains mandatory in these particular patients.